EVALUATION OF THE EFFECTIVENESS OF ENHANCED RECOVERY AFTER SURGERY (ERAS) PROTOCOL ON POSTOPERATIVE OUTCOMES IN GENERAL SURGERY PATIENTS: A PROSPECTIVE COMPARATIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Enhanced Recovery after Surgery (ERAS) protocols are multimodal, evidence-based perioperative care pathways designed to reduce surgical stress, promote early recovery, and improve postoperative outcomes. While ERAS is widely adopted in many surgical specialties, its effectiveness in general surgical procedures in resource-limited settings requires further validation. Aim: To evaluate the effectiveness of ERAS protocol on postoperative outcomes compared with conventional perioperative care in patients undergoing elective general surgical procedures. Materials and Methods: This prospective comparative study was conducted at the Department of General Surgery, Dindigul Medical College and Hospital, over one year (January–December 2023). A total of 200 patients undergoing elective general surgeries were enrolled and allocated into two groups: ERAS group (n=100) and conventional care group (n=100). ERAS included preoperative counselling, carbohydrate loading, early feeding, early mobilization, multimodal analgesia, and avoidance of routine tubes/drains. Primary outcomes assessed were duration of hospital stay, postoperative pain (VAS 12, 24, 48 hours), and return of bowel function. Secondary outcomes included postoperative complications, cost of hospitalization, and 30-day readmission rates. Results: Baseline characteristics were comparable between groups. The ERAS group showed significantly shorter operative duration (p